2018
DOI: 10.1186/s13053-018-0092-2
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-based neoadjuvant chemotherapy in BRCA1-positive breast cancer: a retrospective cohort analysis and literature review

Abstract: BackgroundThere is increasing evidence of high platinum sensitivity in BRCA-associated breast cancer. However, evidence from randomized trials is lacking. The aim of this study was to analyze the results of platinum-based chemotherapy for BRCA1-positive breast cancer in a neoadjuvant setting.MethodsA retrospective study was performed by obtaining information from patient files. The results were compared with the available data from a literature review.ResultsTwelve female patients with BRCA1 gene mutations who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Standard NACT regimens continue to incorporate an anthracycline and taxane-based backbone (3). Recent evidences suggest that a dose-dense chemotherapy regimen, +/− the addition of platinum agents and immunotherapy may positively impact pCR rates in TNBC potentially longer-term outcomes (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Standard NACT regimens continue to incorporate an anthracycline and taxane-based backbone (3). Recent evidences suggest that a dose-dense chemotherapy regimen, +/− the addition of platinum agents and immunotherapy may positively impact pCR rates in TNBC potentially longer-term outcomes (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Some retrospective studies suggested that tumors displayed higher chemosensitivity according to BRCA -mutation status [ 17 , 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Arun et al [ 30 ] compared pCR rates after NAC between BRCA1 or BRCA2 -carriers ( n = 57 and n = 23, respectively) and WT controls ( n = 237).…”
Section: Discussionmentioning
confidence: 99%
“…A key question for clinicians is whether an understanding of the genetic aberrations in hereditary breast cancer can be exploited to improve patient outcomes. The genomic instability induced by mutations in HR genes potentially renders cancer cells susceptible to chemotherapeutic drugs, particularly those that act directly to damage DNA, such as anthracyclines or platinums 82‐88 . In support of this, a number pre‐clinical studies have shown that BRCA1/2 deficient breast cancer cell lines, which lack functional HR, are much more sensitive to platinum‐based drugs, which induce inter‐strand crosslinks 89‐98 .…”
Section: Hr Defects and Cancer Treatmentmentioning
confidence: 99%